Recommendations for a National Research Agenda in UDL: Outcomes From the UDL-IRN Preconference on Research. (December 2019) - Smith, Sean J.; Rao, Kavita; Lowrey, K. Alisa; Gardner, J. Emmett; Moore, Eric; Coy, Kimberly; Marino, Matthew; Wojcik, Brian
Universal Design for Learning (UDL) is a framework that continues to receive increased attention at federal and state levels. The benefits of UDL include providing an approach to curriculum and instructional design that creates flexible instructional goals, methods, materials, and assignments. Despite the growing popularity of UDL in national policies, measuring the implementation of the UDL framework remains elusive. In March 2017, the research committee of the Universal Design for Learning–Implementation and Research Network (UDL-IRN) convened a preconference of researchers and practitioners to discuss and make recommendations for a national research agenda. Four workgroups address issues related to UDL. These included (a) operationalizing and applying UDL, (b) instruments for the measurement of UDL, (c) teacher education/professional development (PD) in UDL, and (d) UDL tools, technologies, and resources. The results of the workgroups' effort to identify issues and strategic actions in UDL implementation and research are reported.